NEOADJUVAN CHEMOTHERAPY RESPONSE TO LOCAL ADVANCED BREAST CANCER PATIENTS AT DR MOHAMMAD HOESIN HOSPITAL PALEMBANG - Aldo Giovanno; Mgs. Irsan Saleh; Nur Qodir; Mulawan Umar (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Breast cancer is a malignancy which invaded breast tissue in the form of ductal or lobular. One most therapy which is given is neoadjuvant chemotherapy. Neoadjuvant Chemotherapy can reduce tumor size so that surgerycan be performed with good breast removal with Modification of Radical Mastectomy (MRM) and Breast Conservative Therapy (BCT). This purpose from this research is to find out neoadjuvant chemotherapy response in Locally Advanced Breast Cancer Patients which has received chemotherapy treatment in RSUP dr Mohammad Hoesin Palembang. This observational descriptive study was conducted at RSUP Mohammad Hoesin Palembang in the period between October until November 2019. The sample of this study was locally advanced breast Cancer patients who underwent chemotherapy that met the inclusion and exclusion criteria. The data were obtained by interviews and observed medical records from the patients which were then analyzed by univariate analysis using SPSS version 25. In this study there were 34 locally advanced breast cancer patients who fulfilled the inclusion and exclusion criteria. 24 of 34 patients (70,6%) received positive response and 10 of 34 patients (29,4%) received negative response.